Comparing the Effects of Frequency Maps on Sentence Perception Between Simulated Bimodal Hearing and Electric Acoustic Stimulation Hearing. - Yoon, Yang-Soo; Nekoutabar, Raha; Dukes, Sydney; Karnik, Trisha; Jahn, Kelly N. (American Journal of Audiology, 2026)
Purpose: Using acoustic simulations of bimodal (BM) and electric acoustic stimulation (EAS) hearing, we investigated if optimal frequency maps differ between these configurations, whether one provides greater benefit, and whether optimal maps vary with the degree of residual hearing. Method: Adults with normal hearing completed sentence perception tasks across frequency maps, simulated hearing configurations (BM vs. EAS), simulated residual hearing bandwidths, and signal-to-noise ratios (SNRs). Acoustic stimulation was simulated with three bandpass filters: 50-250 Hz (A250), 50-500 Hz (A500), and 50-750 Hz (A750). Electric stimulation was simulated with an eight-channel vocoder. The lower boundary of the electric input was shifted to create four maps relative to the acoustic bandwidth: full overlap, narrow overlap (NO), meet, and gap. Results: For BM hearing, the meet map was most effective. For EAS, gap and NO maps yielded the greatest benefits in noise, whereas the meet map performed best in quiet. Optimal maps varied with both residual hearing and SNR. EAS generally outperformed BM hearing at A500 across SNRs, whereas BM hearing performed better at A250 and A750 at -6 dB, and at A750 in quiet. Benefits correlated positively with residual hearing bandwidth. Conclusions: Optimal maps differed between EAS and BM hearing, reflecting distinct acoustic--electric interactions. EAS often provided an advantage, likely due to reduced neural delay mismatches and improved binaural integration. However, no single map was consistently optimal; outcomes depended on residual hearing and SNR, highlighting variability in spectral integration efficiency with available acoustic input.